Decompression technique — A modified approach for lateral alveolar ridge augmentation: A case report - Puisys, Algirdas (Clin Case Rep, 2021)
A particular technique can increase the mucosal and peri‐implant bone thickness, prevent compression around implant neck, and obtain proper space for the following prosthetic treatment with an adequate emergence profile.